Service quality of the prison welfare shop in Maha Sarakham Provincial Prison: Service quality of the prison welfare shop in Maha Sarakham Provincial Prison - Juoisa, Sirasith; Kosonkittiumporn , Saovalak; Kenaphoom, Sanya (RATANABUTH JOURNAL, 2024)
The services provided by prison welfare shops play a vital role in supporting the rehabilitation and adjustment of inmates. These services help foster positive attitudes towards society, which ultimately influences inmates’ reintegration and their ability to lead meaningful lives after release. This study aims to: 1) assess the quality of services provided by the prison welfare shop in Maha Sarakham Provincial Prison, 2) compare the service quality based on gender, age, and length of incarceration, and 3) gather recommendations for improving the shop’s services. This quantitative study sampled 335 inmates at Maha Sarakham Provincial Prison, utilizing a questionnaire with a reliability coefficient of 0.932. Statistical analyses included frequency distribution, percentages, means, standard deviation, t-tests, and one-way ANOVA. The findings revealed that: 1) the overall service quality of the welfare shop was rated at a moderate level ( = 2.61, S.D. = 0.24), 2) perceptions of service quality varied significantly by gender, age, and length of incarceration at a 0.05 level of statistical significance, and 3) recommendations included ensuring adequate stock to meet demand, providing feedback mechanisms for inmates, offering a wider variety of brands for similar products, and selecting courteous, service-minded inmates as shop staff.